2016
DOI: 10.1002/bies.201500116
|View full text |Cite
|
Sign up to set email alerts
|

Has provoking microbiota aggression driven the obesity epidemic?

Abstract: Alterations in the gut microbiome have increasingly been implicated in driving obesity and its associated diseases, but underlying mechanisms remain poorly defined. Herein, in addition to reviewing the field, we hypothesize that a highly significant causative factor of such inflammatory disease-associated microbiome alterations is a more aggressive microbiota that encroaches upon its host, with components having high potential to activate host pro-inflammatory gene expression in a manner that drives metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…The ingestion of DEs, such as carboxymethylcellulose or polysorbate 80, dramatically reduced the mucus layer thickness and was involved in the onset of intestinal inflammation, obesity, and diabetes. These effects were also associated with an increased food intake, from an unknown origin [70].…”
Section: Effects Of Food Additives On Human Gut Microbiotamentioning
confidence: 92%
See 2 more Smart Citations
“…The ingestion of DEs, such as carboxymethylcellulose or polysorbate 80, dramatically reduced the mucus layer thickness and was involved in the onset of intestinal inflammation, obesity, and diabetes. These effects were also associated with an increased food intake, from an unknown origin [70].…”
Section: Effects Of Food Additives On Human Gut Microbiotamentioning
confidence: 92%
“…Most processed foods contain one or more DEs that allow such foods to maintain desired textures and avoid separation into distinct parts. Two DEs, namely carboxymethylcellulose and polysorbate 80, had been demonstrated to promote bacterial overgrowth in the murine SI and facilitate translocation of bacteria across a model gut epithelia [70]. Some authors have suggested that DEs may be one specific factor resulting from industrialization that has resulted in a reduction of GM diversity, altered host-microbiota interactions and, consequently, have contributed to the increased incidence of metabolic syndrome and other inflammatory diseases in industrialized societies [70,71].…”
Section: Effects Of Food Additives On Human Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…It is indeed primordial for the host to keep the intestinal microbiota at a safe distance from the intestinal epithelium, in order to minimize the appearance of tissue damage and inflammation [53]. The intestinal microbiota is restricted to the intestinal lumen by a mucus layer that overlays the epithelium.…”
Section: (C) Intestinal Barrier Maintenancementioning
confidence: 99%
“…maltodextrin or highly branched cyclic dextrin), 9,14 emulsifiers or caseinate salts. All of these have potential downsides: (1) high glycaemic index carbohydrates may increase the insulin response and suppress endogenous lipolysis, 15 (2) emulsifiers can negatively affect GI health 16,17,18 and (3) dairy constituents such as casein are common food allergens. 19 Here, we report on an open-label pilot trial examining the glucose, insulin and BHB responses to an MCT-based sports supplement powder using a digestion-resistant carbohydrate as the sole powder component.…”
Section: Introductionmentioning
confidence: 99%